Between Sudoku rules and labyrinthine paths- A study on design for creative Sudoku learning - Guan-ze Liao; Yi-jyun Shih (Stockholm University Press, 2013)
Sudoku is an intelligence game that has fascinated many people. In addition to offering entertainment, it also attracts players to solve more challenging Sudoku questions. Sudoku novices tend to fail to focus on understanding the operation rules because the grid, words, and numbers of Sudoku are too complicated. The main purpose of this study is to integrate the concept of illustrations of labyrinthine multipath into the interface design of rules teaching of Sudoku to complete the learning design of Sudoku games. The research subjects were a total of 73 elementary school third graders in Miaoli County in Taiwan. The study used a single group pre-test and formal test design to investigate the difference in students' learning effectiveness of Sudoku rules before and after they played Sudoku games. This study used a self-developed ARCS learning motivation scale to analyze the effect of Sudoku game on students' learning motivation, and conducted in-depth interviews with three students with low learning achievement to observe their learning process and how their learning interest was aroused. The results showed that the Sudoku learning design with illustrations of labyrinthine multipath could help students understand Sudoku rules and enhance their learning interest in Sudoku.